A study of plant species suitable for Riverside-Riparian Areas - Villa Juan, Jose Dan (2005)
Transition zones between land and water environments are narrow strips of land called Riparian Areas having a distinct ecosystem. Ecologically, these areas hold great importance in regulating natural cycles between terrestrial and aquatic environments. However these zones are plagued with problems stemming from natural occurrences and those coming from manmade actions.

Specific plant species are looked into and analyzed against given criteria and then tabulated to assess each plant's usefulness against specific needs/problems of riverside-riparian areas. This practice in rating plants creates a system whereby species are applied correctly and with reason.
Keywords: Plants -- Research